Poor ovarian response and the possible role of natural and modified natural cycles - Federica Di Guardo; Christophe Blockeel; Michel De Vos; Marco Palumbo; Nikolaos Christoforidis; Herman Tournaye; Panagiotis Drakopoulos (SAGE Publishing, 2022)
About 20% of women undergoing in vitro fertilization struggle with poor ovarian response, indicating a poor prognosis related to low response following ovarian stimulation. Indeed, poor ovarian response, that is associated with both high cancelation rates and low live birth rates, still represents one of the most important therapeutic challenges in in vitro fertilization. In this context, natural cycle/modified natural cycle- in vitro fertilization, as a 'milder' approach, could be a reasonable alternative to high-dose/conventional ovarian stimulation in poor ovarian responders, with the aim to retrieve a single oocyte with better characteristics that may result in a single top-quality embryo, transferred to a more receptive endometrium. Moreover, modified natural cycle- in vitro fertilization may be cost-effective because of the reduced gonadotropin consumption. Several studies have been published during the last 20 years reporting conflicting results regarding the use of natural cycle/modified natural cycle- in vitro fertilization in women with poor ovarian response; however, while most of the studies concluded that mild stimulation regimens, including natural cycle/modified natural cycle- in vitro fertilization, have low, but acceptable success rates in this difficult group of patients, others did not replicate these findings. The aim of this narrative review is to appraise the current evidence regarding the use of natural cycle/modified natural cycle- in vitro fertilization in poor ovarian responders.